TEAMWORK CLIMATE SCALE (ECTE, in Portuguese): VALIDITY, RELIABILITY AND STANDARDIZATION STUDY - Cibele Correia Semeão Binotto; Márcia Niituma Ogata; Everson Meireles; Jaqueline Alcântara Marcelino da Silva (Universidade Federal do Paraná, 2024)
Objective: to present evidence of validity, reliability, and a standardization procedure for interpreting the Teamwork Climate Scale with family health teams. Method: a methodological study with an exploratory correlational design and a cross-sectional design. The participants were professionals from the Family Health teams of a municipality in the interior of São Paulo - BR. Data collection began in December 2020 and ended in April 2021. Data were analyzed using descriptive and inferential statistics. Results: The fit of the measurement model of four correlated latent factors (Confirmatory Factor Analysis) was acceptable and satisfactory. Composite reliability coefficients were higher than 0.95. It was possible to propose a valuable system of standards for interpreting the results. Conclusion: The study showed evidence of the validity and internal consistency of the Scale, which was confirmed as a powerful instrument whose findings can contribute to strengthening teamwork and interprofessional collaboration.